2013
DOI: 10.1371/journal.pone.0055742
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of PET and Bremsstrahlung SPECT for Imaging the In Vivo Yttrium-90 Microsphere Distribution after Liver Radioembolization

Abstract: BackgroundAfter yttrium-90 (90Y) microsphere radioembolization (RE), evaluation of extrahepatic activity and liver dosimetry is typically performed on 90Y Bremsstrahlung SPECT images. Since these images demonstrate a low quantitative accuracy, 90Y PET has been suggested as an alternative. The aim of this study is to quantitatively compare SPECT and state-of-the-art PET on the ability to detect small accumulations of 90Y and on the accuracy of liver dosimetry.Methodology/Principal FindingsSPECT/CT and PET/CT ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(162 citation statements)
references
References 33 publications
7
148
0
7
Order By: Relevance
“…Elschot et al. demonstrated that time‐of‐flight PET‐based dose estimates were more accurate than SPECT‐based dose estimates, which produced large underestimations in high‐dose regions 15. Conversely, Yue et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Elschot et al. demonstrated that time‐of‐flight PET‐based dose estimates were more accurate than SPECT‐based dose estimates, which produced large underestimations in high‐dose regions 15. Conversely, Yue et al.…”
Section: Discussionmentioning
confidence: 97%
“…Despite positive results from published studies,6, 7 the reported doses assume that the activity distribution within the treatment volume is uniform. Quantitative patient‐specific 90 Y dosimetry has been studied using bremsstrahlung single photon emission computed tomography (SPECT)/computed tomography (CT) 8, 9, 10, 11 and positron emission tomography (PET)/CT 12, 13, 14, 15, 16. However, such dosimetric studies have utilized research software that is not readily available to the medical community and have not illustrated scenarios where voxel‐based dosimetry could be used to predict treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…When combined with SPECT imaging, bremsstrahlung SPECT/CT showed more accurate anatomical localization of 90 Y microspheres [26]. In spite of these characteristics of the bremsstrahlung image, the major drawbacks are the low spatial resolution and long image acquisition time, which would lead to lower tumor-to-normal ratios compared to the 99m Tc MAA images [27].…”
Section: Discussionmentioning
confidence: 99%
“…Other reports revealed that 90 Y PET/CT after 90 Y microsphere treatment has better image quality than 90 Y bremsstrahlung SPECT images [15,26]. The higher resolving power of 90 Y PET/CT might have the potential to predict treatment responses more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…6). Elschot and colleagues [49] showed that the image quality of PET is superior to bremsstrahlung SPECT for the assessment of 90 Y-microsphere distribution after RE. PET showed higher contrast recovery coefficients than SPECT.…”
Section: Post-treatment Imaging Workupmentioning
confidence: 99%